1994
DOI: 10.1111/j.1600-0447.1994.tb01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of post‐stroke depression during the first year in a large unselected stroke population determined using a valid standardized rating scale

Abstract: This study describes the development of post-stroke depression (PSD) prospectively during the first year post-stroke in 285 unselected stroke patients. An appropriate unselected population-based control group without cerebral pathology is included for comparison. Psychiatric assessment with the Hamilton Depression Rating Scale (HDRS) was undertaken unmodified. PSD was defined as HDRS > or = 13. The one-year incidence of PSD among the 209 survivors able to communicate reliably at 1 month was 41%. Most cases dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
117
2
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 23 publications
11
117
2
3
Order By: Relevance
“…In line with previous investigators, 6 -8 we can state that the BDI is an acceptable screening instrument but is not specific enough to be used as a diagnostic tool. In contrast to Andersen et al, 32 we cannot recommend higher cutoff points with patients with stroke. In our study, the sensitivity of the HRSD was lower than that of the BDI, but it showed higher specificity.…”
Section: Discussionmentioning
confidence: 61%
“…In line with previous investigators, 6 -8 we can state that the BDI is an acceptable screening instrument but is not specific enough to be used as a diagnostic tool. In contrast to Andersen et al, 32 we cannot recommend higher cutoff points with patients with stroke. In our study, the sensitivity of the HRSD was lower than that of the BDI, but it showed higher specificity.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, whereas a hospital-based study reported a lower PSD in survivors, from 6 months to 3 years after the onset of stroke, 23 another hospital-based study revealed a decrease in the prevalence of PSD in the 1st year, and a subsequent rise in 2nd and 3rd year, after the onset of stroke. 24 The same pattern of development was revealed by a rehabilitation-based study design, 25 Lack of consensus in scientific opinion on this issue was also evident when the assessment instrument is considered. For instance, assessment for PSD in stroke survivors using Becks Depression Inventory (BDI) revealed no change in the PSD symptoms within 12-15 months after the stroke.…”
Section: Relevance Of Findings To the Fieldmentioning
confidence: 99%
“…Similarly, using a score of 13 or above on the HAM-D, 20 (39.3%) were rated as suffering from clinically significant depression. These cutting points were chosen on the basis of existing work on depression following stroke (Parikh et al, 1988;Andersen et al, 1994) indicating participants ranged from being independent in daily activities to suffering from marked disability and requiring substantial assistance with mobility, feeding and other aspects of self-care. Table 2 shows the informant-rated personality data for the stroke patients.…”
Section: Measures Of Depressionmentioning
confidence: 99%
“…Using cut-off scores of ≥16 on the CES-D (Parikh et al, 1988) and ≥13 on the HAM-D (Andersen et al, 1994) to define depression potentially requiring treatment, odds ratios were calculated for premorbid neuroticism and a past history of mental disorder.…”
Section: Risk Of Depression Conferred By Neuroticism and A History Ofmentioning
confidence: 99%